Benign Symmetric Lipomatosis (Madelung’s disease); A Case Report: Benign Symmetric Lipomatosis (Madelung’s disease); A Case Report - Girapongsa, Luckana; Kiatkungwankai, Pravitpong; Autravisitkul, Orawan; Deesuwun, Pariyanoot (The ASEAN Journal of Radiology, 2025)
Benign multiple symmetric lipomatosis (Madelung’s disease) is a rare disease and characterized by non- capsulated accumulations of fat in a symmetrical manner around the neck and the shoulder, rarely involving the lower limbs and the lower body. The prevalence is increased among the mediteranean ulation and very rare in the oriental area . The etiology is still unknown. We have prest case of madelung disease type I associated with avascular necrosis at both fernoral heads and gyneco- mastia at the right breast.